The impact of credit accessibility on rural households clean cooking energy consumption: The case of Ghana - Martinson Ankrah Twumasi; Yuansheng Jiang; Bismark Ameyaw; Frank Osei Danquah; Monica Owusu Acheampong (Energy Reports, 2020)
This study examined the impact of credit received on rural household clean cooking energy consumption. The study pays more attention to clean energies, such as liquefied petroleum gas (LPG) and kerosene. Due to the endogenous issue of credit, we employed an instrumental variable approach (IV-Probit and IV-Tobit). We analyzed the survey data collected from four regions, Savannah, Bono East, Eastern and central, in Ghana. The result of the econometrics model depicted that household head relationship with an individual in the city, education level, access to off-farm employment, age, household size, and amount of credit received influences the household's probability of consuming and spending on clean cooking energies Concerning the amount of credit received impact on clean cooking energy expenditure, rural households in the eastern region compared to their counterparts were more pronounced. Our findings explored the importance of credit on energy consumption and provided policy implications to enhance clean cooking energy consumption.
Keywords: 330; Clean cooking energy; Credit; Ghana; Instrumental variables